Kurikulum Merdeka Belajar dalam Kajian Filsafat Jean Jacques Rousseau dan Implikasinya Bagi Demokrasi Indonesia - Deonizio Manek; Norbetus Jegalus; Leonardus Mali (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Formal education systems are often trapped in rigid standardization that actually shackles students' creativity and personal uniqueness. This issue raises questions about the extent to which individual freedom is accommodated in modern curricula that tend to be pragmatic. Departing from this issue, this study aims to explore the relevance of Jean-Jacques Rousseau's Romanticism which prioritizes affection and the general will in the context of education. Rousseau argued that the development of science and culture often acts as a chain that restrains humans, thus he proposed the concept of natural education that allows children's instincts to develop freely without damaging cultural intervention. Using qualitative methods based on literature review, this research identified a strong common ground between Rousseau's vision and Indonesia's Freedom to Learn policy. The study reveals that both share a common philosophical foundation: restoring educational sovereignty to institutions and students, allowing them to independently develop their potential, talents, and interests. Therefore, synchronizing Rousseau's ideas with Freedom to Learn serves as a crucial foundation for creating a higher-quality and more humane national education ecosystem.